Contribution of topographic and penetrometric measurements to a site characterization, case of the kekem landslide, national road n°5 (western cameroon) (2010)
Atopographical survey and a dynamic cone penetrometer testing (DCPT) were conducted over the Kekemlandslide area.The aim of the work was to unveil new topographic features of the site, and with the penetrometer soundings predict the depth of the potential rupture surface beneath the damaged area. The analysis of penetrometer data has led to the supposition that the fractured surface interface connecting the basement and sediments has a depth of between 2.00m and 12.20 m. The topographic data was used to determine the average slope percentage over the broken area. The slope percentage gives 33.66% from a point taken over the tearing niche and a point along the road.2Dcontoursmapdrawn with the Surfer software, over an area of 35 hectares has enabled the observation of a step gradient oriented NNE-SSW. Considering the steepness of the slope and the thickness of the sediments, the site remains dangerous for the populations especially during the rainy season.